EVALUASI PROGRAM PEMBINAAN PRESTASI TIM IBL SATYA WACANA SALATIGA: EVALUASI PROGRAM PEMBINAAN PRESTASI TIM IBL SATYA WACANA SALATIGA - Cahyo Wibowo; Dennys Christovel Dese (UNIB Press, 2023)
The achievement coaching program aims to introduce, grow, guide, and develop a personality basis that is balanced, intact, and in harmony to provide knowledge and skills according to talent. Sports teams need the right coaching program to achieve maximum performance. This study aimed to identify, reveal, and evaluate the performance development of the IBL Satya Wacana Salatiga team. The evaluation includes context, input, process, and product. The design used in this research is program evaluation, which uses a quantitative and qualitative approach. In comparison, the model used in this study is the CIPP (Context, Input, Process, Product) model. The subjects in this study are all the administrators, coaches, and athletes of the IBL Satya Wacana Salatiga basketball team. They were directly involved in the achievement coaching program. Data collection techniques were collected using a questionnaire, observation, documentation, and interviews. The data analysis technique study uses quantitative descriptive and the Mile and Huberman interactive analysis model. The results and conclusion of the overall evaluation using the CIPP model for the Satya Wacana Salatiga (SWS) basketball team explained that the achievement coaching program implemented was good. However, there were still some areas for improvement in the SWS basketball team achievement coaching program, starting from facilities and infrastructure, funding, and awards. Evaluation in the coaching process continues to improve from time to time.